Periconceptional Undernutrition in Sheep Affects Adult Phenotype Only in Males - Anne L. Jaquiery; Mark H. Oliver; Maggie Honeyfield-Ross; Jane E. Harding; Frank H. Bloomfield (Journal of Nutrition and Metabolism)
Periconceptional undernutrition (PCUN) in sheep alters fetal growth and metabolism and postnatal growth regulation, but effects on adult body composition are unknown. We investigated the effects of PCUN on adult phenotype. Singleton lambs of ewes fed normally (N, n=17) or undernourished before (UN-61-0 d, n=23), before and after (UN-61-30 d, n=19), or after (UN-2-30d, n=17) mating (d0) were weighed at birth, 12 weeks, and intermittently to adulthood. At the age of 3-4 years, body composition was assessed by dual-emission X-ray absorptiometry followed by postmortem examination. Compared with N animals, male, but not female, offspring of all UN groups had greater % fat mass (all UN versus N: 9±1 versus 2±1%, P<0.001) and perirenal fat (544±36 versus 222±44 g, P=0.002), and proportionately smaller hearts (4.5±0.1 versus 5.2±0.2 g·kg−1), lungs (9.1±0.2 versus 10.6±0.5 g·kg−1), and adrenals (0.06±0.002 versus 0.08±0.003 g·kg−1). UN males also had larger testes (726±21 versus 545±32 g, P=0.007), but UN females had smaller ovaries (2.7±0.08 versus 3.4±0.4 g, P=0.01). Changes were independent of birth weight or postnatal growth velocity. Brief PCUN has sex-specific effects on adult phenotype, predominantly affecting males, which may contribute to adverse metabolic outcomes.